IFN-γ induced IDO and WRS expression in microglia is differentially regulated by IL-4 - Yadav, Manisha C. (2007)
Indoleamine 2,3-dioxygenase (IDO), a tryptophan catabolizing enzyme, has been implicated in the pathogenesis of various neurological disorders. IDO expression is induced by IFN-γ and leads to neurotoxicity by generating quinolinic acid. Additionally, it inhibits the immune response through both tryptophan depletion and generating other tryptophan catabolites. IL-4 and IL-13 have been shown to control IDO expression by antagonizing the effects of IFN-γ in different cell types. Here, we investigated the effects of these cytokines on IDO expression in microglia. Interestingly, we observed that both IL-4 and IL-13 greatly enhanced IFN-γ induced IDO expression. However, tryptophanyl-tRNA synthetase (WRS), which is coinduced with IDO by IFN-γ, is downregulated by IL-4 and IL-13. The effect of IL-4 and IL-13 was independent of STAT-6. Modulation of IDO but not WRS was eliminated by inhibition of protein phosphatase 2A (PP2A) activity. The phosphatidylinositol 3-kinase (PI3K) pathway further differentiated the regulation of these two enzymes, as inhibiting the PI3K pathway eliminated IFN-γ induction of IDO, whereas such inhibition greatly enhanced WRS expression. These findings show discordance between modulations of expression of two distinct enzymes utilizing tryptophan as a common substrate, and raise the possibility of their involvement in regulating immune responses in various neurological disorders.